Space, Religious Diversity, and Negotiation Processes - Lefebvre, Solange (2020)
After a literature review of space, urbanity, and religion, this article identifies some descriptive categories and analytical frameworks to theorize problems faced by religious minorities, especially Muslims, in obtaining space for their cemeteries and places of worship. A second section focuses on debates and an analysis related to these themes in the province of Quebec (Canada), especially in the City of Montreal, showing that while spatial dimensions rarely constitute an analytical category, this aspect is nevertheless a continual source of tension. The article illustrates how dysfunctional administrative processes have dominated the public scene in recent years. A case study shows how a few actors are exploiting provincial regulations in order to oppose public decisions that seek to accommodate the needs of Muslims, using a process for approving amendments to zoning bylaws by way of referendum. After a brief examination of the case related to a Muslim cemetery in a village near Quebec City, to shed light on the recent debates surrounding regulations, the article analyzes the decision-making process resulting in a failure to modify zoning regulations in order to welcome new places of worship in a borough of Montreal. While analyzing administrative and legal aspects, the article also exposes the complexity of the social and spatial dynamics at stake. Our conclusion is that any successful public policy on diversity must employ multilayered strategies, particularly to support space regulations with foundational intercultural and interreligious initiatives. It also brings attention to the perverse effect of some local participatory procedures, whereby a few actors maneuver to mobilize citizens, in order to resist the religious pluralization of space.